2010
DOI: 10.21608/eajbsf.2010.17454
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of Four Volatile Oils on Two Museum Insects Pests

Abstract: Insecticidal effect of volatile oils from peppermint (Mentha piperita), basil (Ocimum basilicum), lemon (Citrus limon) and orange (Citrus sinensis) against two museum insect pests was evaluated by fumigation test. Also, the effect of oils on the antennal segments and their sensilla was studied by using scanning electron microscope. Results of the study revealed that peppermint oil offered the highest toxicity to adults and larvae of the black carpet beetle and cigarette beetle at LD 50 level. Larvae of both sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…According to the LC50 values obtained by them, the highest toxicity was calculated to be 6.68 mg/ml and it was found that it could be effective against aphids. In addition, extracts from different parts of citrus plants Rhyzopertha dominica (Fabricius, 1792) (Coleoptera: Bostrichidae), Sitophilus oryzae Schoenherr, 1838 (Coleoptera: Curculionidae) (Tripathi et al, 2003), Callosobruchus maculates (Fabricius, 1775) (Coleoptera: Chrysomelidae) (El- Sayed & Abdel-Razik, 1991), Tribolium castaneum (Herbst, 1797) (Coleoptera: Tenebrionidae), Trogoderma granarium Everts, 1898 (Coleoptera: Dermestidae) (Zia et al, 2013), Zabrotes subfasciatus Boheman, 1833 (Coleoptera: Chrysomelidae) (Zewde & Jembere 2010), Musca domestica (L., 1758) (Diptera: Muscidae) (Palacios et al, 2009), Planococcus ficus Ben-Dov, 1994 (Hemiptera: Pseudococcidae) (Karamaouna et al, 2013), Thaumetopoea wilkinsoni Tams, 1924 (Lepidoptera: Notodontidae) (Çetin et al, 2006), Attagenus fasciatus (Thunberg, 1795) (Coleoptera: Dermestidae), Lasioderma serricorne (Fabricius, 1792) (Coleoptera: Ptinidae) (Bakr et al, 2010), and mosquitoes (Akram et al, 2010;Effiom et al, 2012) is supported by the literature. Choi et al (2004) determined the toxicity of 53 vegetable oils to Tetranychus urticae C. L. Koch, 1836 (Acari: Tetranychidae).…”
Section: Discussionmentioning
confidence: 99%
“…According to the LC50 values obtained by them, the highest toxicity was calculated to be 6.68 mg/ml and it was found that it could be effective against aphids. In addition, extracts from different parts of citrus plants Rhyzopertha dominica (Fabricius, 1792) (Coleoptera: Bostrichidae), Sitophilus oryzae Schoenherr, 1838 (Coleoptera: Curculionidae) (Tripathi et al, 2003), Callosobruchus maculates (Fabricius, 1775) (Coleoptera: Chrysomelidae) (El- Sayed & Abdel-Razik, 1991), Tribolium castaneum (Herbst, 1797) (Coleoptera: Tenebrionidae), Trogoderma granarium Everts, 1898 (Coleoptera: Dermestidae) (Zia et al, 2013), Zabrotes subfasciatus Boheman, 1833 (Coleoptera: Chrysomelidae) (Zewde & Jembere 2010), Musca domestica (L., 1758) (Diptera: Muscidae) (Palacios et al, 2009), Planococcus ficus Ben-Dov, 1994 (Hemiptera: Pseudococcidae) (Karamaouna et al, 2013), Thaumetopoea wilkinsoni Tams, 1924 (Lepidoptera: Notodontidae) (Çetin et al, 2006), Attagenus fasciatus (Thunberg, 1795) (Coleoptera: Dermestidae), Lasioderma serricorne (Fabricius, 1792) (Coleoptera: Ptinidae) (Bakr et al, 2010), and mosquitoes (Akram et al, 2010;Effiom et al, 2012) is supported by the literature. Choi et al (2004) determined the toxicity of 53 vegetable oils to Tetranychus urticae C. L. Koch, 1836 (Acari: Tetranychidae).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it was found that antidermatophytic activity of P. odoratissimus oil was comparatively satisfactory to the control antifungal drugs fluconazole and griseofulvin against E. floccosum, T. verrucosum, T. violaceum, and T. mentagrophytes. Several studies have shown that P. odoratissimus has antiviral, antiplatelet, anti-inflammatory, antioxidant, antiallergy, and anticancer activity [20][21][22][23][24][25]. Although there is not much literature on the antifungal activity of P. odoratissimus, a study by Singh et al, 2011, has shown that antidermatophytic activity of P. odoratissimus was better than fluconazole [19].…”
Section: Discussionmentioning
confidence: 99%
“…Insecticidal activity of Citrus limon and Citrus sinensis against vine mealybug, Planococcus ficus [9]. The larvicidal and adulticidal effects of Citrus limon and Citrus Essential Oils: A Suite of Insecticidal Compounds DOI: http://dx.doi.org /10.5772/intechopen.95887 Citrus sinensis are mentioned against Attagenus fasciatus and Lasioderma serricorne [10]. The seed and peel extracts of Citrus limon L. was reported to have the highest larvicidal toxicity (LC50 values of 395.59 ppm for seed; 468.69 ppm for peel) after 24 hours over EOs of Citrus grandis, Citrus sinensis, Citrus paradise, Citrus reticulate [11].…”
Section: Citrus Eo Against Insect Spmentioning
confidence: 99%